Sport career in 400 m hurdle run in various groups of the best athletes in the world - Iskra, J.; Przednowek, K.; Walaszczyk, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Sport ontogenesis is a part of participations in training and competition activities. Olympic medallist in mens 400 m hurdle run was 18-23 years old. Training in "low" hurdles (= 400 m hurdles) was started in early school phase (c. 10 years) and was continued even to 40 years (Iskra 2013). Methods: This study regarded the best 400 m hurdlers in the world (n=48, average result: 47.67±0.34 s, age: 25.60±2.14 years). In the analysis hurdlers were divided into two groups, according to the period they developed their personal best results (A=period 1980-99, B=period after 2000). In the analysis we used three basic protocols: (1) chronological development of ones hurdle run results (according to age; from 16 to 39 years old), (2) the basis was the year of personal best result (PB) and (3) following years of athletic development (the length of sport career). Because data distribution was not normal, the non-parametric test U Manna-Whitney a was applied to determine the differences between groups. In research of connections between age and sport results we used Spearmans rank correlation. Results: According to the first protocol, the best results (in both groups) were performed between the age of 25 and 27. Dynamics of sport career in two groups (A1, A2) varied only among 19 years old (approximately 50,82 ± 1,31 v 49,87 ± 1,27 s; p<` 005). In the whole group we observed the highest correlation between the best result and age 27 (r=0.72, p<.01). According to the second protocol the best results in 400 m hurdles start from the 6th year of specialisation and continue till the 11th year of career. In this aspect there are no differences between groups. According to the third protocol in the group of world best 400 m hurdlers we cant accurately predict the best results 1 . 4 years ahead of this time (r=0.41-0.46, p.0.05). Discussion: Each of the human activities has its own "peak performance" (Ericsson, 1993). In the athletic events Olympic medals are won by runners from 17 to 40 years old (Butler 2012). Previous studies showed that the best results in mens 400 m hurdle run obtained in the age of 25 (Dickwach and Wagner, 1997). In our study we observed that this optimal age is 2 years higher. Harsanyi and Martin (1985) claimed that in junior-age category (=19 years old) the best hurdlers obtained 96% of future best records. In our group, in the age of 19 hurdlers obtained 93.7% (A) and 95.7% (B) of their personal records in the future.